2020
DOI: 10.1126/scitranslmed.abc1492
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic HCN4 expression drives mTOR-dependent epilepsy in mice

Abstract: The causative link between focal cortical malformations (FCMs) and epilepsy is well accepted, especially among patients with focal cortical dysplasia type II (FCDII) and tuberous sclerosis complex (TSC). However, the mechanisms underlying seizures remain unclear. Using a mouse model of TSC- and FCDII-associated FCM, we showed that FCM neurons were responsible for seizure activity via their unexpected abnormal expression of the hyperpolarization-activated cyclic nucleotide–gated potassium channel isoform 4 (HCN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 62 publications
6
50
0
Order By: Relevance
“…Neuronal cytomegaly was also consistently reported for the evaluated gene variants. Increased neuron soma size was reported as early as E17.5 (Tarkowski et al, 2019) and persisted into adulthood (Lim et al, 2015(Lim et al, , 2017Park et al, 2018;Ribierre et al, 2018;Nguyen et al, 2019;Zhang et al, 2019;Dawson et al, 2020;Hsieh et al, 2020;Zhong et al, 2021). Furthermore, increasing mTORC1 activity levels by varying concentration of the Rheb S16H plasmid resulted in dose-dependent increases in neuron soma size, supporting a direct relationship between mTORC1 activity level and soma size (Nguyen et al, 2019).…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 78%
See 3 more Smart Citations
“…Neuronal cytomegaly was also consistently reported for the evaluated gene variants. Increased neuron soma size was reported as early as E17.5 (Tarkowski et al, 2019) and persisted into adulthood (Lim et al, 2015(Lim et al, , 2017Park et al, 2018;Ribierre et al, 2018;Nguyen et al, 2019;Zhang et al, 2019;Dawson et al, 2020;Hsieh et al, 2020;Zhong et al, 2021). Furthermore, increasing mTORC1 activity levels by varying concentration of the Rheb S16H plasmid resulted in dose-dependent increases in neuron soma size, supporting a direct relationship between mTORC1 activity level and soma size (Nguyen et al, 2019).…”
Section: Conserved Mtorc1-dependent Phenotypes Across Pi3k-mtor and Gator1 Gene Variantsmentioning
confidence: 78%
“…These studies reported that dysmorphic, cytomegalic neurons within the tissue samples exhibit altered intrinsic excitability that may contribute to the generation of epileptic activity (Cepeda et al, 2003(Cepeda et al, , 2005(Cepeda et al, , 2012Wang et al, 2007). In addition, a recent IUE study in Rheb S16H mutant pyramidal neurons reported that decreasing neuronal excitability by expressing an inwardly-rectifying potassium channel (Kir2.1) significantly reduced seizures, supporting that mutant neurons are directly involved in seizure generation (Hsieh et al, 2020). In light of these findings supporting a cell autonomous mechanism of hyperexcitability, we review the electrophysiological data on neurons expressing the different PI3K-mTOR and GATOR1 gene variants.…”
Section: Potential Shared and Divergent Sources Of Cell-autonomous Hyperexcitabilitymentioning
confidence: 93%
See 2 more Smart Citations
“…AMPK activation downregulates Kir2.1 [291], and we recently found that sustained activation can enhance maturation of contractile and metabolic features of PSC-CMs but also reduces expression of KCNJ2 [292]. In contrast, in neurons, mTOR signaling increases expression of HCN channels [293]. Dysregulation of AMPK and mTOR signaling may affect expression levels of Kir2.1 and HCN4 in cardiomyocytes, leading to cardiomyocyte membrane depolarization.…”
Section: Resting Membrane Potentialmentioning
confidence: 95%